2013
DOI: 10.1002/jcb.24479
|View full text |Cite
|
Sign up to set email alerts
|

miR‐21 modulates the ERK–MAPK signaling pathway by regulating SPRY2 expression during human mesenchymal stem cell differentiation

Abstract: The ERK-MAPK signaling pathway plays a pivotal role during mesenchymal stem cell (MSC) differentiation. Studies have demonstrated that ERK-MAPK promotes adipogenesis and osteogenesis through the phosphorylation of differentiation-associated transcription factors and that it is the only active signaling in all three lineages (adipogenic, chondrogenic, and osteogenic) during MSC differentiation. Recent studies pointed to the significant roles of microRNA-21 (miR-21) during several physiological and pathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
106
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 51 publications
6
106
0
1
Order By: Relevance
“…In this study, we found that the early markers of osteogenesis-related genes, including COLI, COLIII, RUNX2, OPN, and OCN, were upregulated compared with the levels obtained with the naked MAO Ti surface on days 3, 6, and 9, and this upregulation profile presented a time-dependent pattern and a dose-dependent effect. Our results indicated that the coating of CS/HA/miR-21 nanoparticles on the MAO Ti surface via reverse transfection promotes osteogenic differentiation at the mRNA level, which is in accordance with previous studies 16,17 that found that the overexpression of miR-21 can facilitate osteogenesis and accelerate bone fracture healing; furthermore, its target PI3K-AKT-GSK3β pathway may play an important role in the osteogenic differentiation of cells by stabilizing β-catenin according to previous reports. 17 This study confirmed the feasibility of fabricating CS/HA/miR-21 nanoparticle-coated MAO Ti surfaces via reverse transfection and demonstrated their application for the transfection of miR-21 to adjust the fate of hBMMSCs in vitro.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we found that the early markers of osteogenesis-related genes, including COLI, COLIII, RUNX2, OPN, and OCN, were upregulated compared with the levels obtained with the naked MAO Ti surface on days 3, 6, and 9, and this upregulation profile presented a time-dependent pattern and a dose-dependent effect. Our results indicated that the coating of CS/HA/miR-21 nanoparticles on the MAO Ti surface via reverse transfection promotes osteogenic differentiation at the mRNA level, which is in accordance with previous studies 16,17 that found that the overexpression of miR-21 can facilitate osteogenesis and accelerate bone fracture healing; furthermore, its target PI3K-AKT-GSK3β pathway may play an important role in the osteogenic differentiation of cells by stabilizing β-catenin according to previous reports. 17 This study confirmed the feasibility of fabricating CS/HA/miR-21 nanoparticle-coated MAO Ti surfaces via reverse transfection and demonstrated their application for the transfection of miR-21 to adjust the fate of hBMMSCs in vitro.…”
supporting
confidence: 93%
“…16 miR-21 has been found to be highly expressed during osteogenic differentiation, which indicates that this miRNA may repress stemness maintenance in osteoblasts. 16, 17 Ourania et al 18 and Meng et al 17 revealed that the overexpression of miR-21 can accelerate osteogenesis and impair adipogenesis in both human umbilical cord mesenchymal stem cells (MSCs) and human bone marrow MSCs (hBMMSCs); miR-21 may exert its osteogenic function through the PI3K-AKT-GSK3β pathway via the stabilization and accumulation of β-catenin. 17 A key issue in the therapeutic application of miRNAs is safe and highly efficient transfection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have pointed out the significant role of sprouty2, a substrate of Mnk1, during multiple diseases or physiological process such as human mesenchymal stem cell differentiation, 17 papillary thyroid cancer, 18 and prostate cancer progression 19 by regulating ERK signaling pathway. ERK1/2 is one of the most important signaling that could provide new treatment strategies for cardiac hypertrophy and remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In pigs, predicted mRNA targets include among others programmed cell death protein 4 (PDCD4) or ineterleukin 10 (IL10) that further regulate a set of genes critical to cell proliferation and inflammation (Podolska et al 2012). Interestingly, in many cell types miR-21 expression pattern is correlated with ERK-MAPK activity (Mei et al 2013), the intracellular signaling pathways inducing a variety of downstream processes. It was found recently, that DON, besides its effects on cell differentiation and proliferation, may affect the intestinal barrier function through MAPK and claudin proteins (Pinton et al 2009).…”
Section: Spatial and Temporal Changes In Mir Expression During Treatmmentioning
confidence: 99%